Self-efficacy in four language skills of Indonesian L2 learners of English: A comparative survey study - Sinaga, Yohanes Septian; Subekti, Adaninggar Septi (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
The self-efficacy (SE) of second or foreign language (L2) learners, or their belief in their ability to successfully carry out language tasks, can affect their communication behaviours and learning outcomes. This study seeks to explore L2 learners’ SE levels in listening, reading, writing, and speaking, and to determine whether there are significant differences in SE across these four skills. A survey method was used, involving 144 Indonesian L2 learners from non-English departments. The survey included Likert-scale items measuring SE in the four language skills. Descriptive statistics revealed that learners had moderate-to-high SE in reading, listening, and writing, while reporting a higher level of SE in speaking. The mean scores range from 3.2 to 4.6 on a 1-5 scale. Paired-sample t-tests showed that speaking SE was significantly greater than that of reading, listening, and writing, whilst no significant differences were found among the SE of the latter three skills. Based on these findings, it is recommended that teachers promote more balanced development across all four language skills in integrated-skill classes where teachers build learners’ confidence in skills they feel less capable of. Potential contributions include mapping learners’ perceived strengths and weaknesses in L2 learning.